Teachers’ Workload and Class Size as Correlate of Students’ Academic Performance in Selected Secondary Schools in Singida Urban (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to establish the relationship between teachers’ workload, class size and students’ academic performance from five selected secondary schools in Singida urban. The study was guided by three objectives and three research hypotheses. The study employed correlational cross-sectional design. A sample size of two hundred nighty four respondents was randomly chosen from five secondary schools. A self-administered questionnaire was used to collect information from respondents. The collected data were analysed by Statistical Package for Social Scientists (SPSS) using Karl Pearson’s Linear Correlation Coefficient and Multiple Regression Analysis to assess the correlation between teachers’ workload and class size and students’ academic performance. The study results indicated that, there was no significant relationship between teachers’ workload and students’ academic performance in surveying secondary schools in Singida Urban at the five percent level of significance. Further, the findings show that class size was positively correlated with students’ academic performance in secondary schools in Singida urban. Also, there is a significant difference between teachers’ work load and class size in relation to students of academic performance in selected secondary schools in Singida urban. Based on the study findings, it is recommended that, emphasis should be directed at improving class size if teachers and education stakeholders in Singida urban have to increase students’ academic performance. The study concluded class size is found to be the best predictor of students’ academic performance in the surveyed secondary schools in Singida Urban.